2010
DOI: 10.1007/s10549-010-0843-x
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factorβ1 L10P variant plays an active role on the breast cancer susceptibility in Caucasian: evidence from 10,392 cases and 11,697 controls

Abstract: In view of the essential role of transforming growth factorβ1 (TGFB1) on both inhibiting the development of early benign breast tumors as well as promoting tumor invasion, the association of TGFB1 L10P polymorphism and breast cancer risk has been widely reported, but results of previous studies were somewhat contradictory and underpowered. To overcome the limitations of individual study and to understand the real situation, we conducted a systematic review and meta-analysis towards the association between TGFB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 21 publications
3
14
0
Order By: Relevance
“…As many as five meta-analyses (all in 2010) were conducted on this polymorphism (Gu et al, 2010;Huang et al, 2010;Ma et al, 2010;Qi et al, 2010;Qiu et al, 2010) without reaching a consensus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As many as five meta-analyses (all in 2010) were conducted on this polymorphism (Gu et al, 2010;Huang et al, 2010;Ma et al, 2010;Qi et al, 2010;Qiu et al, 2010) without reaching a consensus.…”
Section: Discussionmentioning
confidence: 99%
“…Two of these meta-analysis found no association between TGF-β1 29T/C polymorphism and breast cancer risk (Gu et al, 2010;Huang et al, 2010), while the two others showed no overall association between this SNP and breast cancer risk, but an increased risk of breast cancer with 10P allele in Caucasians (Ma et al, 2010;Qi et al, 2010), and another meta-analysis showed significant association of 10P in overall analysis as well as in the Caucasian group (Qiu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, if there was significant heterogeneity, we used a random effects model to analyze the study. If there was no heterogeneity, we used a fixed effects model [2, 2325]. We also performed Begg’s and Egger’s tests when significant differences ( P  < 0.05) were present to determine if publication bias was also present.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, all five meta-analyses were published in the same year [29], [42], [51], [52], [53]. Two of these meta-analysis stated no association between c.29C>T polymorphism and breast cancer [29], [51], while the two others stated no overall association between this substitution and breast cancer risk, but an increased risk of breast cancer with 10P allele in Caucasians [42], [52], and yet another meta-analysis stated significant association of 10P in overall analysis as well as in the Caucasian group [53]. Contrary to the observations of all these meta-analyses, particularly the latter three, we found the alternate allele (‘T’ or ‘leucine’) to be a risk factor for breast cancer.…”
Section: Discussionmentioning
confidence: 99%